Measuring the content validity of MEPI using content validity ratio - Mohd Noor Norashady, Mohamed Arip Muhammad Aziz Shah, Moh @ Hj Abdullah Eftah, Yon Haniza (Universiti Pendidikan Sultan Idris, 2016)
Measuring the content validity of MEPI using content validity ratio by Mohd Noor Norashady, Mohamed Arip Muhammad Aziz Shah, Moh @ Hj Abdullah Eftah, Yon Haniza,